Kochiites: a look into the intangible heritage of Kochi - Thomas, Bony; Ravi Shankar N. (tr.) (Kochi Pranatha Books, 2018)
This book acts as a portal into the demography of Fort Kochi-Mattancherry area of Kochi, a human habitat for more than 30 migrant societies speaking 16 different languages apart from Malayalam, the common language of Kerala.
Keywords: Intangible heritage of Kochi; Fort - Kochi